The mediating role of e-counselling skills on the relationship between e-counseling ethics and limitations with counselling self-efficacy among e-counsellors in Malaysia - Nor Zainudin, Zaida; Lee, Wei Rong; Asli, Alia Sara; Mohamad Yusop, Yusni; Ahmad, Nor Aniza; Hassan, Siti Aishah (UiTM Press, 2023)
Counselling skills and accountability towards ethical counselling conduct are important characteristics of highly confident and competent counsellors. For the counselling field to remain relevant in the fast-changing world, counsellors must demonstrate high resiliency and adaptability to the current demand and challenges in counselling tasks, including e-counselling. This study aimed to identify e-counselling skills as mediators between e-counselling ethics and e-counselling limitations with counselling self-efficacy among e-counsellors in Malaysia. One hundred and fifty-nine ecounsellors from various Malaysian government and private institutions were recruited to participate in the study. A back-to-back translation technique was employed to adapt the Counselling Self-Estimate Inventory (COSE) and identify e-counsellors’ self-efficacy in the Malaysian context. E-counselling skills, ethics and limitations were measured using self-developed questionnaires for data collection purposes. E-counselling skills, e-counselling ethics, e-counselling limitations, and counselling selfefficacy were all found to be significantly correlated, as predicted by the structural equation model analysis. The findings confirmed the researchers’ assumptions that e-counselling skills play an important role as a mediator between e-counselling limitations and counselling self-efficacy among ecounsellors. The model achieved the goodness of fit indices. The Board of Counsellors Malaysia, counselling program providers, and counsellors at all levels, including trainees, supervisors, and professional counsellors, can benefit from the current findings.